Kemampuan Aktinomiset Menghambat Pertumbuhan Sclerotium rolfsii dan Pembiakannya pada Medium Serbuk Gergaji - Nurul Widyanti; Giyanto Giyanto (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
Antagonistics microorganisms, such as actinomycetes, are potential biological control agents for plant diseases. Mass culture of actinomycetes to provide enough inoculum for field application is sometimes costly. Therefore alternative medium with simple preparation and relatively less costly is required for mass culture of actinomycetes. This research was conducted to evaluate the ability of 4 actinomycetes isolates, i.e. APS 7, APS 9, APS 12, and ATS 5, in suppressing growth of Sclerotium rolfsii in vitro and to assess the growth of actinomycetes in alternatif medium containing organic wastes, i.e sawdust and bran. Among 4 tested isolates of actinomycetes only APS 7 showed its potency as biocontrol agents for S. rolfsii with growth suppression rate of 91.73% after 3 weeks incubation. In general, both sawdust and bran has the potency as culture medium for APS 7. After 8 weeks incubation period the average population of actinomycetes grew in culture medium containing sawdust and bran was 335 x 106 cfu/g and 331 x 106 cfu/g, respectively.Key words: biocontrol agents, bran, organic waste